NUMERICAL MODELING OF THE CINDER FORMATION PROCESS WITH APPLICATION OF SYMMETRICAL IMPLICIT SCHEMA IN MOVING HEATED INGOT OF CHROMIUM STEEL - A. N. Chichko; A. S. Borozdin (Литьë и металлургия, 2005)
The mathematical model for numerical analysis of scaling of the ingots, moving with constant speed in the furnaces with step-heating and given quantity of temperature zones, is offered. The results of computer calculations of temperature and scale layer forming at movement of ingot with constant speed in furnaces with five temperature zones are presented.